Diagnostic impact of CSF biomarkers for Alzheimer's disease in a tertiary memory clinic. Issue 5 (22nd August 2014) - Duits, Flora H.; Prins, Niels D.; Lemstra, Afina W.; Pijnenburg, Yolande A.L.; Bouwman, Femke H.; Teunissen, Charlotte E.; Scheltens, Philip; van der Flier, Wiesje M.
Abstract: Background: We aimed to assess the impact of cerebrospinal fluid (CSF) biomarkers for Alzheimer's disease on decision making and patient management in a tertiary memory clinic. Methods: We included all patients, for 1 year, visiting the VUmc Alzheimer Center for cognitive screening. Neurologists completed questionnaires before and after CSF disclosure. We assessed the change of diagnosis, diagnostic confidence, and impact on patient management. Results: A total of 438 patients (age 63 ± 8 years, 39% women) were included, of whom 351 (80%) underwent lumbar puncture. After the disclosure of CSF 23/351 diagnoses (7%) were changed. Diagnostic confidence increased from 84% to 89% ( P  < .001). There were consequences for management in 44/351 patients (13%) with CSF, and 13/87 patients (15%) because of unavailable CSF. There was no effect of age on these results. Conclusions: CSF biomarkers aid clinicians with decision making during diagnostic work‐up of cognitive disorders. This study may be useful for developing guidelines for the implementation of CSF biomarkers in daily practice.